DoctoralMusicComposition: “KitaNiphon Cholamak”ForSynthesizerChamberOrchestra - Thanachan, Onravadee; Suwannathada, Pimchanok (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
This dissertation discusses on the composition, Kita Niphon Cholamak, for synthesizer and chamber ensemble of four to ten musicians. This composition is an innovation from ethnomusicology aspect that encompasses the cultural and other fundamental dimensions of the Thailand’s Royal barge procession into a new form of program music. The traditional sounds and barge chants performed during the Royal barge procession have been transcribed and combined with Western musical elements to produce a composition comprising of four contrasting movements. Each movement features a different pair of orchestral instruments combined with the synthesizer creating a new program music composition. According to the composition, the synthesizer provides a highly effective orchestral harmony that supports and enhances the main themes in the composition. Crucially, the modern synthesizer’s sophisticated technology adds musical colours, enhances the ceremonial atmosphere invoked by the composition, and brings a unique character to the musical narrative.